(untitled) (Research, Society and Development, 2021)
Based on bibliographical research of specialists in the area of violence and violence against the elderly, as well as in official documents of the Brazilian government, the article aims to bring to the discussion the problem of violence, mistreatment, and abuse suffered by the elderly in the Brazilian context. Brazil undergoes significant and profound changes in its age structure, and the contingent of the elderly only tends to increase. Concomitant with this increase, the same number of challenges that the country tends to face in the face of this reality is growing. A sociological approach is carried out on the theme of violence in order to understand, situate, conceptualize, characterize and problematize violence within the social context and its manifestation in society. To this end, we use the ideas of Norbert Elias, Michel Foucault, Max Weber, Michel Missi, Willem Schinkel, Norberto Bobbio, Edgar Morin, Thomas Hobbes, among others. The text concludes by stating that violence between human beings seems to be part of humanity’s own history, and that domestic violence and abuse of the elderly should not be understood outside the context of social / structural violence in which individuals and communities are inserted. It is, therefore, necessary for society as a whole to have a broader view that allows the perception that coping with violence against the elderly goes beyond criminal analysis and requires the application of the principles that guide the National Policy on the Elderly and the Statute of the Elderly.